Peran Mata Kuliah Microteaching dalam Mengembangkan Keterampilan Guru Mengajar di Kelas - Farah Annisa; Renata Nur Annisa; Tisa Yunita; Tsabitah Rafifah; Yessi Vichaully (Departement of Mathematics Education, 2023)
Teachers are one of the professional workers who need skills in it. One of the basic abilities possessed by a teacher is the ability to teach or teaching skills. The ability to teach becomes a provision for teachers in carrying out their duties to become teachers later. In addition, teaching skills are also one of the important things in achieving learning goals. Teaching skills are skills related to all aspects of teacher abilities related to various teacher duties. Managing and leading classes is not easy, proper exercises and methods are needed; in this study it emphasizes how micro teaching learning can develop the skills needed by teachers later. There are eight skills that teachers need including, explaining skills, questioning skills, skills using a variety of stimulus, strengthening skills, opening, and closing lessons, small group and individual teaching skills, classroom management skills, and guiding small group discussions. In research using descriptive qualitative methods, the data that has been collected is then processed and the results are in the form of explanations.